Spontaneous bacterial peritonitis: update on diagnosis and treatment - Popoiag Roxana-Emanuela; Fierbințeanu-Braticevici Carmen (Sciendo, 2021)
Spontaneous bacterial peritonitis (SBP) is a common complication in patients with liver cirrhosis, with an increased risk of mortality. For this reason, a diagnostic paracentesis should be performed in all patients with ascites and clinical features with high diagnostic suspicion. Although literature data abound in identifying new diagnostic markers in serum or ascites, they have not yet been validated. The final diagnosis requires the analysis of ascites and the presence of > 250 mm3 neutrophil polymorphonuclear (PMN) in ascites. If previous data showed that the most common microorganisms identified were represented by gram-negative bacteria, we are currently facing an increase in gram-positive bacteria and multidrug-resistant bacteria. Although prompt and effective treatment is required to prevent outcomes, this becomes challenging as first-line therapies may become ineffective leading to worsening prognosis and increased in-hospital mortality. In this paper we will make a brief review of existing data on the diagnosis and treatment of SBP.